Pertanggung jawaban Pidana Korporasi Pada Tindak Pidana Perbankan Dalam Rangka Pembaruan Hukum Pidana - Nurjannatul Fadhilah; Aria Zurnetti; Nani Mulyati (Lareh Law Review, 2024)
Previously banking crimes committed by corporations tended to be difficult to enforce, because corporations weren’t the subject of criminal law, either according to the Criminal Code or the Banking Law. In order to reform the national criminal law, the government then promulgated the National Criminal Code and the PPSK Law which introduced a renewal of thought in the Indonesian criminal law regime. The reform led to a shift in the position of corporations as subjects of banking crimes. The issues raised are: 1) How does the position of corporations shift as the subjects of banking crime after the National Criminal Code and the PPSK Law?; 2) How is corporate criminal liability in banking crimes after the National Criminal Code and the PPSK Law? This research uses normative juridical methods through statue approach, and conceptual approach. The results obtained from this study include that after the National Criminal Code and the PPSK Law, the position of corporations as subjects of banking crimes has shifted from previously not recognized in the Criminal Code or Banking Law, now it has been recognized as a subject of banking crimes, so that the principle of delinquere non potest university used by the previous Criminal Code is no longer relevant in the new Indonesian criminal law paradigm. Then the National Criminal Code and the PPSK Law basically use three forms of corporate criminal liability, namely: criminal liability is imposed on corporations only, criminal liability is imposed on individual only, or liability is imposed on both (corporation and individual).